Ongoing Transposon-Mediated Genome Reduction in the Luminous Bacterial Symbionts of Deep-Sea Ceratioid Anglerfishes - Tory A. Hendry (American Society for Microbiology, 2018)
ABSTRACT Diverse marine fish and squid form symbiotic associations with extracellular bioluminescent bacteria. These symbionts are typically free-living bacteria with large genomes, but one known lineage of symbionts has undergone genomic reduction and evolution of host dependence. It is not known why distinct evolutionary trajectories have occurred among different luminous symbionts, and not all known lineages previously had genome sequences available. In order to better understand patterns of evolution across diverse bioluminescent symbionts, we de novo sequenced the genomes of bacteria from a poorly studied interaction, the extracellular symbionts from the “lures” of deep-sea ceratioid anglerfishes. Deep-sea anglerfish symbiont genomes are reduced in size by about 50% compared to free-living relatives. They show a striking convergence of genome reduction and loss of metabolic capabilities with a distinct lineage of obligately host-dependent luminous symbionts. These losses include reductions in amino acid synthesis pathways and abilities to utilize diverse sugars. However, the symbiont genomes have retained a number of categories of genes predicted to be useful only outside the host, such as those involved in chemotaxis and motility, suggesting that they may persist in the environment. These genomes contain very high numbers of pseudogenes and show massive expansions of transposable elements, with transposases accounting for 28 and 31% of coding sequences in the symbiont genomes. Transposon expansions appear to have occurred at different times in each symbiont lineage, indicating either independent evolutions of reduction or symbiont replacement. These results suggest ongoing genomic reduction in extracellular luminous symbionts that is facilitated by transposon proliferations. IMPORTANCE Many female deep-sea anglerfishes possess a “lure” containing luminous bacterial symbionts. Here we show that unlike most luminous symbionts, these bacteria are undergoing an evolutionary transition toward small genomes with limited metabolic capabilities. Comparative analyses of the symbiont genomes indicate that this transition is ongoing and facilitated by transposon expansions. This transition may have occurred independently in different symbiont lineages, although it is unclear why. Genomic reduction is common in bacteria that only live within host cells but less common in bacteria that, like anglerfish symbionts, live outside host cells. Since multiple evolutions of genomic reduction have occurred convergently in luminous bacteria, they make a useful system with which to understand patterns of genome evolution in extracellular symbionts. This work demonstrates that ecological factors other than an intracellular lifestyle can lead to dramatic gene loss and evolutionary changes and that transposon expansions may play important roles in this process.